CORAL REEF COVER RELATIONSHIP TO POMACENTRIDAE AND PHYTOPLANKTON CORAL FISH IN KASIAK ISLAND OF WEST SUMATRA PROVINCE - Sitohang, Margaretha; Nurrachmi, Irvina; Thamrin, Thamrin (Asian Journal of Aquatic Sciences, 2021)
Kasiak Island is one of the islands located in the waters of Pariaman, West Sumatra, and located right in front of Pariaman City. Around the sea, the island is surrounded by coral reefs and is a protected area. In the aquatic area of Kasiak Island has never been conducted research on the relationship of coral reef cover to the coral Pomacentridae and phytoplankton. Therefore, it is necessary to conduct research on this matter in the waters of Kasiak Island, West Sumatra Province. Data collection of coral reef cover is done by the LIT (Line Intercept transect) method with a transect length of 50 meters at a depth of 5 meters using scuba equipment. Coral fish observation is done by UVC (Underwater Visual Census) method with a transect length of 50 meters and an observation area of 2.5 meters left and right at a depth of 5 meters. Phytoplankton sampling is conducted during the day at 11.00 to 15.00 WIB at five points of the station with a depth of 5 meters using Vandorn water sampler volume 2 L with a total take of 100 L, then filtered using Plankton net no 25 and inserted into a sample bottle of 125 ml, then preserved using Lugol 4% as much as 4-6 drops, after which analyzed in the laboratory. Based on the results there is a very strong relationship between coral cover to the abundance of coral fish, where coral cover contributes to the abundance of coral fish by 93.87%, which means that the higher the percentage of coral cover the more species and abundance of coral fish are found. Then the a strong relationship between coral reef cover and phytoplankton abundance, where coral reef cover contributes to the abundance of phytoplankton by 56.37%, which means an increase in the percentage of coral reef cover along with the increasing abundance of phytoplankton.